FORMULASI DAN PENINGKATAN SIFAT KELARUTAN MINUMAN SERBUK COKELAT - Yulianto Hartono; Sugiyono Sugiyono; Nur Wulandari (Jurnal Teknologi dan Industri Pangan, 2018)
Chocolate beverage powder (CBP) consists of cocoa powder, sugar and milk powder and their compositons are important for consumer’s acceptance. Generally, wettability due to the hydrophobicity of the cocoa butter is a problem and lecithination is often used to improve the wettability. Because CBP pro-duction process utilizes dry blending method, the incorporation of lecithin is a challenge. There of this stu-dy, aimed to (1) formulate CBP produced by dry blending as well as to (2) improve its wettability using pre-pared soy (de-oiled) lecithin powder and soy liquid lecithin. A hedonic test using 50 respondents was carried out to obtain the preferred formula. Two methods of lecithin addition were tested (i) premixing with cocoa powder and (ii) direct addition during dry blending process. Liquid lecithin was added by spraying at 70°C to the material during dry blending. The amount of prepared lecithin added were 0.5, 2.0, and 4.0% for lecithin powder and 0.5, 1.0, 2.0, 2.5, and 3.0% for liquid lecithin. The results showed that the formula with the highest overall like (6.7) was that containing 40% instant whole milk powder, 40% sugar castor, 10% alkalized cocoa powder, 9.7% maltodextrin and 0.3% salt. It was clearly showed that liquid lecithin was more effective in improving wettability as compared to lecithin powder and there was no significant differences between premixing and direct addition method. The amount of prepared liquid lecithin needed to meet the wettability target of below 30 seconds the selected formula without giving significant difference in taste was 25%.